Comparison of insecticide sprays in alternate rows and in all rows on Asian citrus psyllid control and Huanglongbing progress in sweet orange orchards - Primiano, Isabela V; Barbosa Junior, Jonas Tadeu; Bassanezi, Renato Beozzo (Plant disease, 2024)
One strategy to reduce Huanglongbing (HLB) is controlling its insect vector, the Asian citrus psyllid (ACP) Diaphorina citri, by preventive insecticide sprays. The recommendation is to spray insecticide in all rows (conventional spray - CONV), but some growers empirically spray in alternate rows (ALT) to increase the spray frequency without increasing the operating cost. Therefore, this work compared the effect of ALT with CONV on the ACP population and HLB incidence. The spray deposition (amount of metallic copper per leaf area), coverage (percentage of water-sensitive paper area covered by spray), and efficacy (ACP mortality) of each treatment were also evaluated on both sides of the trees. Two field trials were performed: Trial #1 compared ALT every 7 days (ALT7) with CONV every 14 days (CONV14), and trial #2 compared different spray frequencies of ALT with CONV every 7 days (CONV7). In trial #1, no differences were observed in the ACP population or HLB progress between ALT7 and CONV14 after 5 years. In trial #2, ALT7 presented the highest percentage of ACP and cumulative HLB incidence than CONV7 and ALT every 3 to 4 days, after 2 years. Hence, when the frequency of ALT was half the frequency of CONV, similar results were observed. Spray deposition, coverage, and efficacy were similar between tree sides in CONV, but they were uneven in ALT, resulting in higher values on the tree side that directly received the spray. Insecticide spray should be performed with the frequency enough to keep new shoot protected during their growth.